Environmental Considerations for the Management of the Bivalve Fisheries of Bahía Magdalena (Mexico), a Coastal Lagoon at the Southern End of the California Current - Jiménez-Quiroz, María del Carmen; Barrón-Barraza, Francisco Javier; Cervantes-Duarte, Rafael; Funes-Rodríguez, René (Frontiers in Marine Science, 2021)
This study presents an overview of bivalve assemblages in Bahia Magdalena (México) and the possible impact of environmental variability on these populations, constantly stressed by fishing. This lagoon is responsible for a high proportion of regional bivalves' harvest. Based on eight commercially exploited species, we described the composition of the bivalve assemblage and its biological characteristics, the fishery history, and environmental variability in the marine area adjacent to the lagoon (1970-2019) and bivalves habitat (2002-2020). The data sources were public databases and published literature. The enlisted species (n=184) belong to 6 orders, and most are small and infaunal, but the assemblage structure is unknown. The fisheries began at different times and focused on the most valuable resources. Almost all bivalves' harvest had had wide variations due to intensive fishing and a weak regulation frame. After 2015, the main resources were the Pacific wing-oyster (a new resource since 2017) and the geoduck clam because of declining other resources’ abundance (e.g., pen shells. Pacific calico scallop). There was a warming trend in the region since the 1970s, but the strongest ENSO phases caused the most notable changes before 2013; after that year, a combination of large-scale phenomena increased the temperature significantly. The Chlorophyll-a abundance trend negatively correlated with temperature, but there is an almost constant supply of particulate organic matter in the BM interior. After 2015, the lagoon's water quality gradually deteriorated, and in 2017 and 2019, harmful algal blooms occurred, but its impact was not fully assessed. The challenges faced by the fishery are multiple (institutional weakness, regional warming); however, permanent monitoring programs of environmental conditions and critical biological variables should be implemented to design scenarios that allow fishery sustainability.